Prototipo de un Sistema en GNS3 con la Integración de Asterisk y PostgreSQL sobre IPv6 para Consulta de Notas Académicas - Salcan Chisaguano, Cristian Fernando (2024)
In the present investigation, a system prototype was implemented in GNS3 to integrate Asterisk and PostgreSQL over IPv6 for consulting academic notes. It begins by investigating the technologies that allow this integration and thus achieving the implementation of the prototype and its subsequent evaluation of its performance, using two functional scenarios: the first through the direct connection of Asterisk to the PostgreSQL database using ODBC and the second through integration to the database using Webservice with the Asterisk AGI module. The Zoiper softphone is used as the end user for functional tests to consult notes through implementing an IVR in Astersisk. The type of research is quantitative since indicators such as response time, latency, and resource use have been defined to measure performance in the two integration scenarios using the SIPp effort tool. When comparing the two integration options for consulting academic notes, it was found that the direct connection to the database offers better performance in terms of response time and latency, with differences of 9.15 ms and 1.8 ms, respectively. Additionally, a slight difference in system resource usage was observed, with 1.74% more CPU usage and a minimal 0.04% increase in RAM usage compared to the integration of WebService AGI. These findings offer important technical information to apply this integration solution to different educational areas or, failing that, adapt it to other concurrency requirements in areas other than education.